Sovereign rating changes : how they affected the stock markets of the PIIGS countries during the European sovereign debt crisis - Candeias, João Eduardo Dias (2015)
The focus of this paper is to study the effect of sovereign rating changes in the PIIGS (Portugal, Italy, Ireland, Greece and Spain) national stock markets during the European sovereign debt crisis. In my research I find that (1) downgrades convey more information to the market than upgrades. (2) The reaction varies between countries; with only Greece having a significant market reaction on the event day and with Italy and Spain not having a discernible reaction to the announcements. (3) The reactions differ depending on the agency that subscribed the announcement, with only S&P downgrades producing a significant market reaction on the day of the announcement and with Moody’s and Fitch upgrades producing significant reaction but only the day after the announcement. (4) Finally, I establish that Greece downgrade announcements don’t spillover to Portuguese and Irish stock markets.